Combination Therapy for Metastatic Renal Cell Carcinoma: A Systematic Review and Network Meta-analysis. (July 2020) - Alam, Muhammad U.; Jazayeri, Seyed B.; Gautam, Shiva; Norez, Daniel; Kumar, Jatinder; Tanneru, Karthik; Nguyen, Sabine; Costa, Joseph; Bandyk, Mark; Ganapathi, Hariharan P.; Koochekpour, Shahriar; Balaji, K.C.
Abstract : Introduction: Randomized clinical trials have shown combination therapy to be superior in progression-free survival (PFS) rates when compared with sunitinib alone. However, there have been no direct comparisons among the combination strategies making it unclear as to which may be the preferred option. We performed a network meta-analysis of the combination therapy (immune checkpoint inhibitor plus axitinib or bevacizumab) used in metastatic renal cell carcinoma (mRCC) and provided a rank order preference based on PFS, and adverse events (AEs). Materials and Methods: A systematic search on the treatment of mRCC using combination therapy till July 2019 was done. Studies reporting on combination therapies with immune checkpoint inhibitor plus axitinib or bevacizumab for mRCC were selected. Frequentist method was used for rank order generation. Results: A total of 3 studies consisting of 2672 patients were selected. All combination therapies demonstrated improved PFS when compared with sunitinib alone. The rank order for PFS showed combination of pembrolizumab plus axitinib had the highest probability of favorability followed by avelumab plus axitinib and atezolizumab plus bevacizumab (surface under the cumulative ranking 0.9, 0.7, and 0.4, respectively). For AEs, pembrolizumab plus axitinib had the least AEs ≥grade 3, followed by avelumab plus axitinib and atezolizumab plus bevacizumab (surface under the cumulative ranking 0, 0.5, 1.0). Conclusions: This network meta-analysis demonstrates that combination of pembrolizumab plus axitinib may be the preferred option based on efficacy and side effect profile compared with avelumab plus axitinib or atezolizumab plus bevacizumab. However, all the 3 combination strategies were superior to sunitinib alone in improving PFS in patients with mRCC. Abstract : Supplemental Digital Content is available in the text.